Pemetaan Tingkat Kerawanan Banjir Menggunakan Sistem Informasi Geografis (SIG) di Kota Samarinda - Yenrico Octapian Octapian; Yulian Widya Saputra; Aisyah Trees Sandy; Mei Vita Romadon Ningrum (Dinasti Research, 2026)
Floods are a hydrometeorological disaster that frequently occurs in urban areas, including Samarinda City, which has a low-lying topography and crosses the Mahakam River. This study aims to map the level of flood vulnerability in Samarinda City using a Geographic Information System (GIS). The method used is a quantitative approach with GIS-based spatial analysis through scoring, weighting, and Weighted Overlay techniques. The parameters described include elevation, slope gradient, distance to the river, land use, rainfall, and soil type. The results show that areas with a high level of flood vulnerability reach 59.73% of the total study area, mainly displayed along the banks of the Mahakam River and lowlands with dense organization. The level of moderate vulnerability covers 36.92%, while low vulnerability only 3.35%. The main factors causing vulnerability are high rainfall, gentle slopes, proximity to the river, and the conversion of infiltration land into built-up areas. The resulting vulnerability map can be the basis for strategies for local governments in disaster-aware spatial planning and flood mitigation. This research contributes to the development of disaster GIS studies and increasing the adaptive capacity of the community to flood risks in Samarinda City.